Comparative analysis of behavior of the «bone – fixator – endoprosthesis» system for I–III type internal hemipelvectomy reconstruction with and without the use of a metal bar - Kostiuk, Viktor; Lazarev, Igor; Diedkov, Anatolii; Skiban, Maxim (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective: to study the changes of the biomechanical system «bone – fixator – endoprosthesis» under the loading for internal hemipelvectomy I–III type Enneking with reconstruction of the pelvic ring defect by a metalcement spacer with and without reinforcement with a metal bar. Methods: spatial geometry of the pelvis is reconstructed with the software package «Mimics». Data are obtained by calculating Mises values. Results: the stresses on the screws in the model were not significantly (0.27 %) larger (σmах 132.6 MPa vs. 132.3 MPa in the model without reinforcement) and did not exceed the strength limit. The maximum value of stress on polymethylmethacrylate in both models is localized in the place of contact with the pubic symphysis and is not significantly (0.4 %) higher in the model with the bar (σmах — 24.7 and 24.6 MPa, respectively). The maximum values of stress on the sacral bone in both models are defined in the zone of proximal screw installation in the lateral mass of the sacral bone, but 5 % larger in the construction without a bar — 10.6 and 10.1 MPa. The maximum permissible loads were: on the sacral bone in a model with a bar of 1.06 body weight, without a bar — 1.01; for polymethylmethacrylate — 3.05 and 3.03 body weight respectively; for metal screws — 3.44 and 3.43 body weight, respectively. Conclusions: the usage of a metal bar in the system «bone – fixator – endoprosthesis» for internal hemipellectomy type I–III does not change the mechanical strength and stability of the model. The most susceptible to destruction was the lateral area of the sacrum in the place of the proximal screw, which should be strengthened by inserting an additional screw into the upper part of the sacroiliac joint. In the dynamics (walking, running, climbing stairs), the load of the surgery site can be 4 times higher the weight of the body, which due to the linear growth of stress values can lead to the destruction of the structure and requires the usage of additional means of support (crutches, a stick, etc.).